2020
DOI: 10.1182/blood.2019002227
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic angiogenesis in the bone marrow of humanized sickle cell mice is reversed by blood transfusion

Abstract: Sickle cell disease (SCD) is a monogenic red blood cell (RBC) disorder with high morbidity and mortality. Here, we report, for the first time, the impact of SCD on the bone marrow (BM) vascular niche, which is critical for hematopoiesis. In SCD mice, we find a disorganized and structurally abnormal BM vascular network of increased numbers of highly tortuous arterioles occupying the majority of the BM cavity, as well as fragmented sinusoidal vessels filled with aggregates of erythroid and myeloid cells. By in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 89 publications
2
38
0
1
Order By: Relevance
“…In patients with SCD, we confirmed the presence of vitamin D deficiency, despite the oral vitamin D supplementation [30]. Different factors have been invoked to explain the persistent vitamin D deficiency in SCD patients independently from vitamin D supplementation such as (i) the dark skin type present in 50% of our patients that may hinder the effect of solar radiation in vitamin D production [31]; (ii) reduced vitamin D intestinal absorption, most likely related to chronic cholestasis which may affect enterohepatic circulation of bile acids with reduced absorption of liposoluble compounds such as vitamin D [32]; (iii) increased body fat tissue levels in SCD patients could further induce vitamin D deficit by sequestration, thus determining its low bioavailability [12,[33][34][35]. In our cohort, we showed that 72% of patients had vitamin D level <30 ng/mL and that hypovitaminosis D was confirmed even after supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with SCD, we confirmed the presence of vitamin D deficiency, despite the oral vitamin D supplementation [30]. Different factors have been invoked to explain the persistent vitamin D deficiency in SCD patients independently from vitamin D supplementation such as (i) the dark skin type present in 50% of our patients that may hinder the effect of solar radiation in vitamin D production [31]; (ii) reduced vitamin D intestinal absorption, most likely related to chronic cholestasis which may affect enterohepatic circulation of bile acids with reduced absorption of liposoluble compounds such as vitamin D [32]; (iii) increased body fat tissue levels in SCD patients could further induce vitamin D deficit by sequestration, thus determining its low bioavailability [12,[33][34][35]. In our cohort, we showed that 72% of patients had vitamin D level <30 ng/mL and that hypovitaminosis D was confirmed even after supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with SCD, recurrent infarcts of bone and bone-marrow (BM), compensatory medullary hyperplasia associated with bone marrow niche vascular abnormality contribute local to insufficient oxygen and nourishment supply [2,10]. This results in intra BM sickling worsening local hypoxia, which may negatively impact mesenchymal stem cell compartment as well as the related osteoblast recruitment [11,12]. The biocomplexity of SBD is further increased by the presence of vitamin D deficiency, a condition very frequent also in the whole population, children and adults [13] which increased resorptive state and to a subsequent reduction in bone mineral density (BMD) [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…12 A study by Park et al showed that the pathologic angiogenesis seen in mice with SCD could be reversed by a 6-week blood transfusion targeting sickle hemoglobin (HbS) to 30%. 13 Leonard et al found that bone marrow from patients with SCD is characterized by inflammation, aggregation, and stress erythropoiesis, leading to suboptimal recovery of CD34+ cells. 14 gene editing is considered a reasonable approach for use at this time, an appropriations rider from Congress currently prohibits germline modifications in humans.…”
Section: Session I: Therapeutic Potential Of Modified Hscsmentioning
confidence: 99%
“…BM microenvironment is also important to support normal and pathologic erythropoiesis [30,31]. β-thalassemia is a globally distributed, hereditary erythroid disorder, caused by the absence or decreased production of the β-globin chain.…”
Section: Introductionmentioning
confidence: 99%